Lexical strata and vowel (dis)harmony - Walter, Mary Ann (Linguistica (Ljubljana), 2016)
In this study I explore the phonological behavior of the hypocoristic suffix (...) in Turkish. Such a suffix is common to many of the Balkan languages. Turkish differs in its introduction of the front vowel variant of the suffix, presumably to satisfy the vowel harmony requirements in Turkish for backness and rounding in high vowels. However, in spite of the potentially alternating suffix allomorphs, collection of naturalistic data as well as of elicited survey data reveals that the majority of nickname outputs are disharmonic. I conclude that the Turkish data provides further evidence for Ito and Mester's (2009) key insight that different strata of the lexicon may operate according to different rules/constraint rankings. However, the Turkish data is not consistent with their specific faithfulness-based approach. The hypocoristic lexical stratum exhibits a greater number of vowel harmony violations, but not due to more faithfulness to vowel inputs/underlying forms. Rather, the harmony violations in this stratum are gratuitous - I argue, precisely in order to distinguish this stratum from the lexicon at large. An approach such as Pater's (2010) indexed constraints model better accommodates this type of lexical variation.
Keywords: disharmonie vocalique; emprunts; fonologija; hipocoristique; ljubkovalni izrazi; phonologie; prevzete besede; samoglasnik; samoglasniška disharmonija; turc; turščina; voyelle